درجة ممارسة معلمي المدارس الأساسية الحكومية لمهارات التفكير الناقد في محافظة عجلون من وجهة نظر المعلمين أنفسهم - محمود, هناء; الفريحات, نايف (University of Eloued جامعة الوادي, 2018)
هدف هذه الدراسة إلى الكشف عن درجة ممارسة معلمي المدارس الأساسية الحكومية لمهارات التفكير الناقد في محافظة عجلون من وجهة نظر المعلمين أنفسهم, وقد تكونت عينة الدراسة من (183) معلما ومعلمة. وتوصلت الدراسة إلى النتائج الآتية: _ وجود فروق ذات دلالة إحصائية في آراء أفراد العينة حول درجة ممارسة معلمي المدارس الأساسية الحكومية لمهارات التفكير الناقد ككل يعزي إلى متغير الجنس لصالح الإناث. _ عدم وجود فروق ذات دلاله إحصائية في آراء أفراد حول ممارسة معلمي المدارس الأساسية الحكومية لمهارات التفكير الناقد تعزى إلى متغير(المؤهل العلمي، سنوات الخبرة The aim of this study was to detect the degree of government school teachers for the basic skills of critical thinking in Ajloun from the point of view of the teachers themselves, and study sample consisted of 183 male and female teachers. The study found the following results: -There were statistically significant differences in the views of respondents about the degree of government school teachers for the basic skills of critical thinking as a whole due to the differences in the sex variable in favor of females. - There were no statistically significant differences) in views of the members on the practice of teachers in government schools for basic critical thinking skills due to a variable (educational qualification, years of experience).
The Practice Degree of critical thinking skills for the public basic School Teachers in Ajloun Governorate from the perspective of the Teachers Themselves
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 03 جامعة الوادي
Keywords: درجة الممارسة، المدارس الأساسية, مهارات التفكير الناقد; practice degree, basic schools, critical thinking skills